2019
DOI: 10.1101/597765
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

New β-Lactamase Inhibitors Nacubactam and Zidebactam Improve the In Vitro Activity of β-Lactam Antibiotics Against Mycobacterium abscessus Complex Clinical Isolates

Abstract: The new diazabicyclooctane-based β-lactamase inhibitors avibactam and relebactam improve the in vitro activity of β-lactam antibiotics against Mycobacterium abscessus complex (MABC). Here, we evaluated the in vitro activity of two newer diazabicyclooctane-based β-lactamase inhibitors in clinical development, nacubactam and zidebactam, with β-lactams against clinical isolates of MABC. Both inhibitors lowered the MICs of their partner β-lactams, meropenem (eight-fold) and cefepime (two-fold), and those of other … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The aim of our study was to evaluate the activity of nacubactam or zidebactam in combination with ␤-lactams against drug-resistant clinical isolates of MABC. This study is available in bioRxiv (17). Nacubactam and zidebactam were procured from MedKoo Biosciences, Inc., NC, USA (purity Ͼ98%).…”
Section: Nct03630094mentioning
confidence: 99%
“…The aim of our study was to evaluate the activity of nacubactam or zidebactam in combination with ␤-lactams against drug-resistant clinical isolates of MABC. This study is available in bioRxiv (17). Nacubactam and zidebactam were procured from MedKoo Biosciences, Inc., NC, USA (purity Ͼ98%).…”
Section: Nct03630094mentioning
confidence: 99%
“…Currently, the IMP-relebactam combination is undergoing phase III trials, and the meropenem-vaborbactam combination is already available in the market. This established and effective combination opens the door to using potent β-lactams for the treatment of Mab infections (Kaushik et al, 2019b). Furthermore, more recent DBO class β-lactamase inhibitors, including nacubactam, zidebactam, and durlobactam, have been suggested as potent β-lactamase inhibitors that can restore susceptibility to β-lactams against Mab in vitro (Dubée et al, 2015a;Lefebvre et al, 2017;Meir et al, 2018;Le Run et al, 2019;Kaushik et al, 2019b;Dousa et al, 2022).…”
Section: β-Lactammentioning
confidence: 99%
“…This inhibition leads to a reduction in the minimum inhibitory concentration (MIC) of carbapenems and cephalosporins against Mab to clinically achievable levels. Currently, avibactam is exclusively marketed in combination with the cephalosporin ceftazidime under the name Avycaz in the United States (Dubée et al, 2015a;Lefebvre et al, 2017;Meir et al, 2018;Le Run et al, 2019;Kaushik et al, 2019b;Dousa et al, 2022). Furthermore, Dousa et al have demonstrated the effectiveness of two new non-β-lactam-based β-lactamase DBO inhibitors, relebactam and vaborbactam, when evaluated in combination with various commercially available β-lactams against clinical isolates of Mab.…”
Section: β-Lactammentioning
confidence: 99%
“…Whether combinations of avibactam with β‐lactam antibiotics will show potential in the clinical treatment of M. abscessus pulmonary disease remains to be determined. It is noteworthy that several other β‐lactamase inhibitors developed in recent years, including nacubactam, zidebactam, relebactam, and vaborbactam, are now being actively studied against M. abscessus in the hope they will be stronger potentiators of the activity of β‐lactam antibiotics 143‐145 …”
Section: Repurposable Drugs Versus M Abscessus Complex: Play To Losementioning
confidence: 99%